Designing data-intensive Web applications - Ceri, Stefano 1955- (2003)
The most prominent Web applications in use today are data-intensive. Scores of database management systems across the Internet access and maintain large amounts of structured data for e-commerce, on-line trading, banking, digital libraries, and other high-volume sites. Developing and maintaining these data-intensive applications is an especially complex, multi-disciplinary activity, requiring all the tools and techniques that software engineering can provide. This book represents a breakthrough for Web application developers. Using hundreds of illustrations and an elegant intuitive modeling la.
Includes bibliographical references (pages 543-550) and index. - Print version record
Keywords: Web site development; Application software -- Development; Database management; Sites Web; Développement; Logiciels d'application; Développement; Bases de données; Gestion; COMPUTERS; Data Processing; Application software; Development